Tools for the Implementation of LEL and Scenarios (TILS) - Gil, Gustavo Daniel (2002)
In most experiments carried out in Requirement Engineering based on the methodology suggested by Leite [Leite95], the developer invested too much time in activities that had nothing to do with the construction itself, since administration of the data obtained had to be done. In this paper a tool to support the LEL production is presented. This tool incorporates an integrated environment between the Discourse Universe, LEL and Scenarios with hypertext technology to facilitate the surfing between the different elements [Leite90]. This allows a much more flexible interaction in the surfing and administration of the data obtained which enables us to know all the vocabulary of the application domain. In addition, this tool allows the automatic generation of a list of preliminary scenarios.